Correlação entre os planos cefalométricos e a linha vertical verdadeira em telerradiografias de perfil obtidas na posição natural de cabeça em pacientes com padrão facial I, II e III - Miguita, Márcio Roberto Tadano (2007)
This study evaluated the relationship between cephalometric planes and the true vertical line on lateral cephalograms obtained in natural head positioning, from individuals with different facial patterns. The sample comprised 28 individuals (15 females and 13 males), aged 17 to 37 years, with complete dentition at least up to the first molars without previous orthodontic/surgical treatment. The patients were divided into three groups according to the different facial patterns, namely Pattern I, Pattern II and Pattern III, according to Capelozza Filho (2004). Lateral cephalograms were obtained from the individuals in natural head positioning (NHP) with projection of a metallic line to define the true vertical line (TVL). After cephalometric tracing, classical reference planes (SN, Frankfurt plane, Palatal plane, Occlusal plane and Mandibular plane) were analyzed in relation to the TVL, in order to determine the correlation between cephalometric planes in facial patterns I, II and III. There was no statistically significant difference between values observed for the planes SN, FRANK, PP and GoGn for the three facial patterns investigated. The reference plane SN, widely employed in several cephalometric analyses, presented a variance of 25.9º. The horizontal planes in relation to the TVL did not present any specific behavior for each type of facial patter, suggesting that more than one reference plane should be employed in individuals with dentofacial deformity, as well as other measurements to allow a complementary sagittal evaluation.